Prevalence of weight-loss strategies and use of substances for weight-loss among adults: a population study Prevalência de estratégias de emagrecimento e uso de substâncias para perder peso entre adultos: um estudo populacional - Eduardo Coelho Machado; Mariângela Freitas da Silveira; Vera Maria Freitas da Silveira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This paper concerns a cross-sectional population-based study conducted with adults living in the city of Pelotas, Rio Grande do Sul State, Brazil. It aims to determine the prevalence of weight-loss practices and use of substances for weight-loss during the 12 months preceding the interview. The prevalence of weight-loss attempts was 26.6%. Although dietary control and regular physical exercise were the most commonly used strategies, the prevalence of the combined use of these methods was only 36% for individuals trying to lose weight. The prevalence of use of substances for weight-loss was 12.8% (48.4% of those who tried to lose weight). The use of dietary control and substances was more common among women, while men practiced physical exercise with greater frequency. Teas were the most frequently used substances for weight-loss. Multivariate analysis identified being female, excess weight and self-perception of excess weight as major associated factors for the use of substances for weight-loss. Finally, we found that, although weight-loss attempts are common, the majority of obese individuals do not make attempts to lose weight and only a minority follows the recommended practices. Estudo transversal de base populacional conduzido com adultos residentes na cidade de Pelotas, Rio Grande do Sul, Brasil, que objetivou determinar a prevalência de práticas de emagrecimento e uso de substâncias para emagrecer, nos últimos 12 meses antes da entrevista. A prevalência de tentativas de emagrecimento foi de 26,6%. Controle dietético e prática regular de exercícios físicos foram as estratégias mais frequentes, mas apenas 36% daqueles que tentaram emagrecer combinaram-nas. A prevalência do uso de substâncias para emagrecer foi de 12,8% (48,4% daqueles que tentaram emagrecer). Mulheres utilizaram controle dietético e substâncias mais frequentemente do que homens, enquanto estes utilizaram mais exercícios físicos. As substâncias de uso mais frequente foram os chás. A análise ajustada identificou sexo feminino, excesso de peso e percepção do excesso de peso como os maiores fatores associados ao uso de substâncias. Assim, identificamos que tentativas de emagrecimento são frequentes, porém, não são referidas pela maioria dos obesos e apenas uma minoria daqueles que tentam emagrecer segue as práticas recomendadas.